2016
DOI: 10.1167/iovs.16-19419
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dry Eye Disease on Work Productivity, and Patients' Satisfaction With Over-the-Counter Dry Eye Treatments

Abstract: Dry eye causes negligible absenteeism, but markedly reduces workplace and non-job-related performances. Impairment of work performance is more closely linked to dry eye symptoms than to clinical signs. Patients' perceptions of OTC dry eye medication tend to be more positive than their perceptions of symptom relief.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 32 publications
0
52
0
1
Order By: Relevance
“…-Work capacity: Many published works support dry eye disease to have negative effects on concentration [7,8] and decreased productivity [1,13,14]. More specifically, studies found dry eye to reduce workplace [13,14] and nonjob related [13] performances and create substantial loss to work industry [14].…”
Section: Level Of Independence -Activities Of Daily Livingmentioning
confidence: 99%
See 1 more Smart Citation
“…-Work capacity: Many published works support dry eye disease to have negative effects on concentration [7,8] and decreased productivity [1,13,14]. More specifically, studies found dry eye to reduce workplace [13,14] and nonjob related [13] performances and create substantial loss to work industry [14].…”
Section: Level Of Independence -Activities Of Daily Livingmentioning
confidence: 99%
“…-Participation in and opportunities for recreation/ leisure: Dry eye disease can negatively affect nonjob related [13] activities including sports where fluctuating visual acuity due to poor tear film dynamics can compromise one's accuracy of visual tracking and fixation ability on moving targets whilst incorporating hand eye coordination.…”
Section: Environmental Impact -Financial Resourcesmentioning
confidence: 99%
“…Although the recall periods may differ, it is striking that the self‐reported prevalence of DE symptoms in offices roughly has remained the same during the last three decades, despite the continuous development of low‐emitting building materials and consumer products, and the advancement of ventilation strategies. The high prevalence of DE symptoms results in substantial productivity work loss or disruption in the order of some percentage; furthermore, DE symptoms deteriorate quality of life …”
Section: Introductionmentioning
confidence: 99%
“…2,31,32 MGD is the leading cause of DED in the United States and elsewhere in the developed world, affecting 5% to 30% of the population aged 50 or older. 3,33 Age-related changes in human MGs include primary acinar atrophy and/or inspissation of MG orifices leading to decreased meibum secretion. MG atrophy and dropout can apparently occur as early as 25 years of age, and the extent of these pathogenic changes increases significantly and approximately linearly with age.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of DED is estimated to be 7% to 34% of the US population, and the number of affected persons is increasing with the aging of our population. 13 The hallmark of DED is tear film instability, caused by a reduction of aqueous tear secretion, and an increase in tear evaporation, either alone or in combination. 1,4 The most common cause of evaporative DED is meibomian gland dysfunction (MGD), which is associated with a decrease in the quantity and/or quality of lipids in tear film.…”
mentioning
confidence: 99%